Protecting Minority Children against Intersectional and Multiple Discrimination - Rashidi, Narges; Sharifi Tarazkouhi, Hosein (Bioethics and Health Law Journal (BHL), 2026)
Minority children - those under the age of 18 belonging to ethnic, religious, linguistic or national minorities - face distinctive vulnerabilities in the global human rights landscape. While all children require heightened protection due to their dependence on others for survival and development, minority children frequently endure discrimination shaped by overlapping identities such as disability, gender or migration background. These intersecting disadvantages restrict their access to education, healthcare and protection, perpetuating cycles of exclusion. This paper critically examines how intersectional and multiple discrimination affect minority children and demonstrates that existing legal frameworks, despite broad guarantees of equality, insufficiently address these compounded harms. By drawing on intersectionality theory and international human rights law - particularly the Convention on the Rights of the Child (CRC) - the study highlights significant protection gaps and their real-world consequences. The significance of this research lies in bridging a critical gap between abstract legal commitments and the lived realities of minority children. It underscores the urgent need for data-driven, inclusive and intersectionally- informed policies that recognize the full complexity of children’s identities. By offering concrete recommendations for policymakers, international organizations and civil society, this paper advances a more effective child rights agenda—one that moves beyond formal equality to ensure substantive justice and dignity for all children.